Knowledge, attitude and purchasing behavior of Saudi mothers towards food additives and dietary pattern of preschool children - Almoabadi, Reem H.; Hanbazaza, Mahitab A. (PeerJ, 2024)
Background There are over 506 children’s products containing one or more types of additives. Maternal awareness of these additives is essential for the health of preschool-aged children, as this period is vital for children’s growth and development. This study aims to assess the knowledge, attitudes, and purchasing behaviors related to food additives among mothers living in the western region of Saudi Arabia, as well as the dietary patterns of preschool children. Method A cross-sectional study was conducted using an online survey with a convenience sample of 521 mothers of preschool-aged children (3–5 years old). The survey gathered data on the child’s age, number of children, the youngest child’s weight and height, food intolerance, tooth decay, as well as the dietary patterns of preschool children. It also assessed the mother’s knowledge, attitude, and purchasing behaviors related to food additives. Results The study found that 46.6% of mothers demonstrated good knowledge of food additives, while 56.0% demonstrated fair attitudes and 78.5% good purchasing behavior regarding additives. Additionally, the majority of mothers reported favorable dietary patterns for their preschool-aged children. “Biscuits and crackers” had the highest consumption frequency (4.98 ± 1.50), with 36.7% of children consuming them once daily, while “Soft beverages” had the lowest consumption frequency (2.73 ± 2.04), with 46.6% of children never consuming them. Statistically significant differences were identified between mothers’ knowledge and their age, education level, occupation status, and economic status (p < 0.05). ANOVA results also indicated a statistically significant difference between mothers’ attitudes and occupation status (p < 0.05). Furthermore, there were significant positive correlations between mothers’ knowledge of food additives and their attitudes (r = 0.293) and purchasing behaviors (r = 0.284) related to additives. Conclusion The findings suggest that mothers possess a relatively good level of knowledge of food additives and hold fair attitudes toward them, tending to result in healthier purchasing behaviors and dietary practices for their preschool-aged children. To increase awareness, nutrition intervention programs are required across various socio-economic groups of mothers in the western region of Saudi Arabia. These programs can significantly contribute to promoting healthier dietary practices for preschool-aged children and improving overall family health and well-being.
Keywords: Food additives; Knowledge; Attitude; Purchasing behavior; Mothers; Preschool children